Graded motor imagery modifies movement pain, cortical excitability and sensorimotor function in complex regional pain syndrome. Issue 4 (25th September 2021) - Strauss, Sebastian; Barby, Silke; Härtner, Jonas; Pfannmöller, Jörg Peter; Neumann, Nicola; Moseley, G Lorimer; Lotze, Martin
Abstract: Patients with complex regional pain syndrome suffer from chronic neuropathic pain and also show a decrease in sensorimotor performance associated with characteristic central and peripheral neural system parameters. In the brain imaging domain, these comprise altered functional sensorimotor representation for the affected hand side. With regard to neurophysiology, a decrease in intracortical inhibition for the sensorimotor cortex contralateral to the affected hand has been repetitively verified, which might be related to increased primary somatosensory cortex functional activation for the affected limb. Rare longitudinal intervention studies in randomized controlled trials have demonstrated that a decrease in primary somatosensory cortex functional MRI activation coincided with pain relief and recovery in sensorimotor performance. By applying a randomized wait-list control crossover study design, we tested possible associations of clinical, imaging and neurophysiology parameters in 21 patients with complex regional pain syndrome in the chronic stage (>6 months). In more detail, we applied graded motor imagery over 6 weeks to relieve movement pain of the affected upper limb. First, baseline parameters were tested between the affected and the non-affected upper limb side and age-matched healthy controls. Second, longitudinal changes in clinical and testing parameters were associated with neurophysiological and imaging parameters. During baseline short intracortical inhibition, as assessed with transcranial magnetic stimulation, was decreased only for hand muscles of the affected hand side. During movement of the affected limb, primary somatosensory cortex functional MRI activation was increased. Hand representation area size for somatosensory stimulation in functional MRI was smaller on the affected side with longer disease duration. Graded motor imagery intervention but not waiting, resulted in a decrease of movement pain. An increase of somatosensory hand representation size over graded motor imagery intervention was related to movement pain relief. Over graded motor imagery intervention, pathological parameters like the increased primary somatosensory cortex activation during fist movement or decreased short intracortical inhibition were modified in the same way as movement pain and hand performance improved. No such changes were observed during the waiting period. Overall, we demonstrated characteristic changes in clinical, behaviour and neuropathology parameters applying graded motor imagery in patients with upper limb complex regional pain syndrome, which casts light on the effects of graded motor imagery intervention on biomarkers for chronic neuropathic pain. Abstract : In this randomized wait-list control crossover study, Lotze et al test possible associations of clinical, imaging and neurophysiology parameters in CRPS patients in the chronic stage over 6 weeks of graded motor imagery. Lotze et al here describe the value of biomarkers assessed for monitoring interventions and predict treatment outcome. Graphical Abstract: